Phenytoin-induced encephalopathy in a child - Mehndiratta, Sumit (Indian J Pharmacol, 2016)
Phenytoin is a commonly used antiepileptic medication in the pediatric age group, but it has a narrow therapeutic range. Various adverse effects have been reported commonly. We report a relatively rare case of encephalopathy in a child from overdose of injectable phenytoin due to ignorance of the previous treatment. Scrutiny of medical records and history is of utmost importance while administering such medications.